Strength of slab-column connections with openings transferring biaxial unbalanced moments - Geng, Jianzeng. (2008)
The purpose of this research program is to investigate the punching behavior of slab-column connections experimentally and analytically, considering the effects of biaxial unbalanced moments, openings, and also elongated column sections. For this purpose, two series of experimental work have been carried out, one analytical model and one semi-empirical method have also been developed to predict the punching shear capacity of general slab-column connections.